Does Watching a Play about the Teenage Brain Affect Attitudes toward Young Offenders? - Blakey, Robert (Frontiers in Psychology, 2017)
Neuroscience is increasingly used to infer the cognitive capacities of offenders from the activity and volume of different brain regions, with the resultant findings receiving great interest in the public eye. This field experiment tested the effects of public engagement in neuroscience on attitudes towards offenders. Brainstorm is a play about teenage brain development. Either before or after watching this play, 728 participants responded to four questions about the age of criminal responsibility, and the moral responsibility and dangerousness of a hypothetical young or adult offender. After watching the play, participants perceived the young offender as less likely to reoffend than the adult offender and the young, but not adult, offender as less morally responsible for his actions, especially on the first offence. Therefore, public engagement in the newest arrival to the criminological scene – neuroscience – may shift support for different youth justice responses.